(untitled) (Ustozlar uchun, 2025)
In the contemporary educational landscape, the development of self-methodological competence is crucial for future English language teachers. This competence encompasses the ability to analyze, design, and adapt teaching strategies independently while considering students’ psychological and social dynamics. This article proposes a holistic and innovative approach integrating philosophical reflection, radical mindset, metacognition, intuition, subconscious awareness, worldview expansion, and student ego regulation. A conceptual model is presented that links cognitive, affective, and philosophical dimensions to enhance methodological autonomy, creativity, and emotional intelligence in teacher trainees. Practical recommendations for teacher education programs are provided.